Social Disclosure In The Annual Reports Accounting Vision About The Corporate Social Responsibility - Mohamed BOULESNAM (Dirassat Journal Economic Issue, 2013)
The purpose of this article is to study the social disclosure in the annual reports in the accounting vision about the corporate social responsibility, we studied the Ahli Bank, through the outputs we reached the following results:Social disclosure includes four main categories: Environment, Energy, Community Involvement, product, Human Resources.Environmental, Employees, Social Investment, Customers, Health and safety, disclosure, are all types of social disclosures existing in the annual and social reports of Al Ahli Bank. We have also found a great development in the amount of social disclosure in the financial reports of Al Ahli Bank during the period studied. And during 2010,2011 Al Ahli Bank started dealing with the separated social reports, and this allowed wide view or (clearer viewing) of social events in the bank.